Metaphor: the power of signification in teaching - Cosimo Laneve; Rosatilde Margiotta (Universidade Federal de Uberlândia, 2022)
This article presents a discussion about the application of metaphors in the meaning of words as an original way of interpreting the world due to the ability of this linguistic resource to adapt to the multiplicity of being, with its different meanings. It was intended to define the concept of metaphor bringing the vision of Aristotle (1987), as well as delimiting the reflexes of the adoption of terms and words for figurative representation. The potential for cognitive abstraction of metaphors that arises from associations is evidenced and ends up enriching and valuing hermeneutic pluralism in everyday expression and also in scientific language.